Comparison of Halmágyi–Curthoys Head Impulse (Thrust) Test with Romberg’s Test in Detection of Vestibular Hypofunctioning in Vertigo Patients - Santhosh Kumar Rajamani; Radha Srinivasan Iyer; Anusha Venkatraman (Journal of Otorhinolaryngology, Hearing and Balance Medicine, 2024)
This study aimed to compare the diagnostic efficacy of the Halmágyi–Curthoys head impulse (thrust) test and Romberg’s test in detecting vestibular hypofunctioning among two groups of 50 vertigo patients each; the two groups were randomly assigned. The assessment utilized the visual analog scale (VAS) to quantify subjective experiences of vertigo. The results revealed distinctive patterns in the detection of vestibular hypofunctioning, highlighting the strengths and limitations of each test. The Halmágyi–Curthoys head impulse test demonstrated utility in identifying vestibular hypofunctioning and its effect on vestibulo–ocular reflexes, particularly in cases with sudden head movements. Romberg’s test was useful in assessing postural instability in vestibular hypofunctioning due to defects in vestibulospinal reflexes. The integration of VAS scores provided valuable subjective insights into the patient experience. This comparative analysis contributes to a nuanced understanding of diagnostic tools for vestibular hypofunctioning in vertigo patients, offering clinicians valuable information for tailored assessments and interventions.